Observatório Cuidativo Virtual: Uma ferramenta no auxílio ao desenvolvimento do bem-estar e da resiliência entre cuidadores - Neves , Leandro Bresciani das; Dias , Leandro Weige; Tavares , Tatiana Aires; Azambuja , Flávia Braga de; Oliveira , Stefanie Griebeler; Costa, Vinicius da (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
This paper presents the development of a dynamic web tool to promote the well-being and resilience of family caregivers within the city of Pelotas. The Virtual Care Observatory (VCO) presents an interface aimed at family caregivers, where it can access support content and interact with other users and another part in which the health professional can consult, manipulate data dynamically, analyze them or still export them for analysis with mining software and data visualization. First, this web platform seeks to be a channel connecting family caregivers to others in similar conditions as well as to the professionals involved. Then, help the day-to-day work of professionals who previously collected the data manually, allowing integration and easy access to caregiver data. Finally, be a platform to support the free software initiative, since only free tools are used for its development. Using the sample record of sixty people to apply data mining with WEKA, the caregiver profiles grouping can be done taking into account factors such as gender, age, and health and life conditions of the caregivers. The VCO was developed within the UFPEL Wordpress Institutional platform, using the Participative Design methodology where prototypes were developed, evaluated and tested until the final version was obtained.